Polarizing plate with pressure-sensitive adhesive layer and image display device
The polarizing plate with an adhesive layer, featuring a specific refractive index difference between its layers, addresses the issue of light leakage in display devices with narrow or omitted bezels by effectively preventing edge light leakage.
Patent Information
- Application Number
- JP2020152615
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-20
- Filing Date
- 2020-09-11
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2040-09-11
AI Technical Summary
The challenge is to prevent light leakage from the edges of polarizers in display devices with narrow bezels, reduced bezel heights, or bezel-less designs, where the polarizer edges are exposed.
A polarizing plate with an adhesive layer is designed, comprising a polarizing film, a first cured material layer, a first resin film, and a pressure-sensitive adhesive layer, where the absolute difference in average refractive index between the first cured material layer and the first resin film is 0.03 or less.
This configuration effectively suppresses light leakage from the polarizing plate edges, even when viewed from angles as high as 85 degrees, ensuring minimal light leakage in display devices with reduced or omitted bezels.
Smart Images

Figure 0007649633000002 
Figure 0007649633000003 
Figure 0007649633000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate with a pressure-sensitive adhesive layer and an image display device including the polarizing plate. [Background technology]
[0002] A polarizing plate has a structure in which a protective film is laminated on at least one surface of a polarizing film via an adhesive layer. The polarizing plate is generally incorporated into a display device via a pressure-sensitive adhesive layer (for example, Patent Document 1). In general, such a display device is provided with a metal frame called a bezel to protect the periphery of the display device in order to suppress external impacts. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2009-42383 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, there has been a trend for display devices to be slimmer and have larger screens. In response to this trend, it has been proposed to increase the size of the display screen even for display devices of the same size by narrowing the bezel width, lowering the bezel height, or omitting the bezel. However, it has been found that when a polarizing plate is incorporated into a display device in which the bezel width is narrowed, the bezel height is lowered, or the bezel is omitted, the edge of the polarizing plate incorporated into the display device is exposed, and light emitted from the backlight or organic light-emitting element may leak from the edge of the polarizing plate when the display device is turned on. [Means for solving the problem]
[0005] The present invention includes the following inventions. [1] A polarizing plate with a pressure-sensitive adhesive layer, comprising a polarizing film, a first cured material layer, a first resin film, and a pressure-sensitive adhesive layer in this order, The polarizing film and the first cured material layer are in direct contact with each other, the first cured material layer and the first resin film are in direct contact with each other, the first resin film and the pressure-sensitive adhesive layer are in direct contact with each other, A polarizing plate with a pressure-sensitive adhesive layer, in which the absolute value of the difference between the average refractive index of the first cured material layer and the average refractive index of the first resin film is 0.03 or less. [2] The polarizing plate according to [1], wherein the first cured material layer is a cured material of an active energy ray-curable composition. [3] The polarizing plate according to [1] or [2], wherein the first cured material layer has a refractive index of 1.55 or less. [4] The polarizing plate according to any one of [1] to [3], wherein the first resin film includes a film formed from a thermoplastic resin. [5] The polarizing plate according to any one of [1] to [4], wherein the first resin film has a thickness of 6 μm or more. [6] The polarizing plate according to any one of [1] to [5], further comprising a second resin film on the surface of the polarizing film opposite to the first cured product layer via a second cured product layer. [7] An image display device comprising: an image display panel; and the pressure-sensitive adhesive layer-attached polarizing plate according to any one of [1] to [6], which is disposed on the viewing side of the image display panel. Effect of the Invention
[0006] The polarizing plate of the present invention can suppress light leakage from the ends of the polarizing plate even when incorporated into a display device with a narrow bezel width, a low bezel height, or a display device that omits the bezel. [Brief description of the drawings]
[0007] [Figure 1] 1 is a cross-sectional view showing a configuration of one embodiment of a polarizing plate of the present invention. [Diagram 2] 1 is a cross-sectional view showing a configuration of one embodiment of an image display device of the present invention. [Diagram 3]4A and 4B are cross-sectional views illustrating a method for checking light leakage in the image display device of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.
[0009] The configuration of one embodiment of the polarizing plate of the present invention will be described with reference to Fig. 1. In the polarizing plate 10 of the present invention, a first cured material layer 2 and a first resin film 3 are laminated in this order on one surface of a polarizing film 1. In addition, the polarizing plate of the present invention may have a configuration in which a second resin film 5 is provided via a second cured material layer 4 on the surface of the polarizing film 1 opposite to the first cured material layer 2, as shown in Fig. 2. In addition, the polarizing plate may be laminated with a panel 7 via a pressure-sensitive adhesive layer 6 to form a display device 30. Each of the components constituting the polarizing plate of the present invention will be described in detail below.
[0010] [Polarizing plate with adhesive layer] The polarizing plate with a pressure-sensitive adhesive layer of the present invention comprises a polarizing film 1, a first cured material layer 2, a first resin film 3, and a pressure-sensitive adhesive 6 in this order. In the polarizing plate with a pressure-sensitive adhesive layer of the present invention, the absolute value of the difference between the average refractive index of the first cured material layer 2 and the average refractive index of the first resin film 3 is 0.03 or less. Furthermore, the polarizing film 1 and the first cured material layer 2 are in direct contact, the first cured material layer 2 and the first resin film 3 are in direct contact, and the first resin film 3 and the pressure-sensitive adhesive layer 6 are in direct contact. In the present invention, the average refractive index refers to the average refractive index at a wavelength of 589 nm.
[0011] In the pressure-sensitive adhesive layer-attached polarizing plate of the present invention, the absolute value of the difference between the average refractive index n2 of the first cured material layer 2 and the average refractive index of the first resin film 3 is 0.03 or less, preferably 0.025 or less, more preferably 0.02 or less, and even more preferably 0.01 or less. When the difference between the average refractive index of the first cured material layer 2 and the refractive index of the first resin film 3 satisfies this range, light leakage from the ends of the polarizing plate can be effectively suppressed when the polarizing plate is used in a display device. The light leakage from the edge of the polarizing plate in the present invention, explained with reference to FIG. 3, refers to the phenomenon that when the display device 30 is turned on and the display device is viewed from an angle inclined by θ (°) in the cross-sectional direction from the front of the display device, the light emitted from the display device leaks out from the cross-section of the polarizing plate, causing the cross-section of the polarizing plate to appear shiny. The larger θ (for example, 15° to 90°) tends to make the light leakage more noticeable, and when θ exceeds 40° (particularly when θ exceeds 80°), the light leakage is significantly noticeable. According to the pressure-sensitive adhesive layer-attached polarizing plate of the present invention, the light leakage from the polarizing plate can be suppressed even when the display device is viewed from an angle of θ of 30° to 90° (particularly 40° to 90°, particularly 80° to 90°).
[0012] <First cured material layer> The first cured layer 2 is not particularly limited as long as the average refractive index difference with the first resin film is within a predetermined range, but is usually a layer formed from a resin composition, and is a cured layer of the resin composition. Specifically, the first cured layer 2 may be a layer formed from a pressure-sensitive adhesive composition (pressure-sensitive adhesive layer), a layer formed from a water-based adhesive composition, a layer formed from an active energy ray-curable adhesive composition, etc. Among them, a layer formed from an active energy ray-curable adhesive composition (cured layer of the active energy ray-curable adhesive composition) is preferable because the average refractive index can be easily adjusted.
[0013] The active energy ray curable adhesive composition is a composition that is cured by irradiation with active energy rays. Examples of the active energy ray curable adhesive composition include a cationic polymerizable active energy ray curable adhesive composition containing a cationic polymerizable compound and a cationic polymerization initiator (hereinafter, sometimes referred to as a photo-cationically polymerizable curable adhesive composition), a radical polymerizable active energy ray curable adhesive composition containing a radical polymerizable compound and a radical polymerization initiator (hereinafter, sometimes referred to as a photo-radical polymerizable curable adhesive composition), an active energy ray curable adhesive composition containing both a cationic polymerizable compound and a radical polymerizable compound and blended with a cationic polymerization initiator and a radical polymerization initiator, and an electron beam curable adhesive composition that is cured by irradiating an electron beam to an active energy ray curable adhesive that does not contain an initiator.
[0014] The cationic polymerizable compound refers to a compound or oligomer that undergoes cationic polymerization reaction and hardens when exposed to active energy rays such as ultraviolet light, visible light, electron beams, and X-rays, or when heated, and specific examples include epoxy compounds, oxetane compounds, vinyl compounds, etc. The active energy ray-curable adhesive composition may use two or more types of cationic polymerizable compounds.
[0015] An epoxy compound is a compound having one or more (preferably two or more) epoxy groups in the molecule. Examples of the epoxy compound include alicyclic epoxy compounds, aromatic epoxy compounds, and aliphatic epoxy compounds.
[0016] Alicyclic epoxy compounds are compounds having one or more epoxy groups bonded to an alicyclic ring in the molecule, such as 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, 3,4-epoxy-6-methylcyclohexylmethyl 3,4-epoxy-6-methylcyclohexanecarboxylate, ethylene bis(3,4-epoxycyclohexanecarboxylate), bis(3,4-epoxycyclohexylmethyl) adipate, and bis(3,4-epoxy-6-methylcyclohexylmethyl). adipate, diethylene glycol bis(3,4-epoxycyclohexyl methyl ether), ethylene glycol bis(3,4-epoxycyclohexyl methyl ether), 2,3,14,15-diepoxy-7,11,18,21-tetraoxatrispiro[5.2.2.5.2.2]henicosane, 3-(3,4-epoxycyclohexyl)-8,9-epoxy-1,5-dioxaspiro[5.5]undecane, 4-vinylcyclohexene dioxide, limonene dioxide, bis(2,3-epoxycyclopentyl)ether, and dicyclopentadiene dioxide.
[0017] The aromatic epoxy compound is a compound having an aromatic ring and an epoxy group in the molecule, and examples thereof include bisphenol-type epoxy compounds or oligomers thereof, such as diglycidyl ether of bisphenol A, diglycidyl ether of bisphenol F, and diglycidyl ether of bisphenol S; novolac-type epoxy resins, such as phenol novolac epoxy resin, cresol novolac epoxy resin, and hydroxybenzaldehyde phenol novolac epoxy resin; polyfunctional epoxy compounds, such as glycidyl ether of 2,2',4,4'-tetrahydroxydiphenylmethane and glycidyl ether of 2,2',4,4'-tetrahydroxybenzophenone; and polyfunctional epoxy resins, such as epoxidized polyvinylphenol.
[0018] Aliphatic epoxy compounds are compounds having at least one oxirane ring (three-membered cyclic ether) bonded to an aliphatic carbon atom in the molecule. Examples include monofunctional epoxy compounds such as butyl glycidyl ether and 2-ethylhexyl glycidyl ether; bifunctional epoxy compounds such as 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and neopentyl glycol diglycidyl ether; trifunctional or higher epoxy compounds such as trimethylolpropane triglycidyl ether and pentaerythritol tetraglycidyl ether; and epoxy compounds having one epoxy group bonded directly to an alicyclic ring and an oxirane ring bonded to an aliphatic carbon atom, such as 4-vinylcyclohexene dioxide and limonene dioxide.
[0019] The oxetane compound is a compound containing one or more oxetane rings (oxetanyl groups) in the molecule. Specific examples include 3-ethyl-3-hydroxymethyloxetane (also called oxetane alcohol), 2-ethylhexyloxetane, 1,4-bis[{(3-ethyloxetan-3-yl)methoxy}methyl]benzene (also called xylylene bisoxetane), 3-ethyl-3[{(3-ethyloxetan-3-yl)methoxy}methyl]oxetane, 3-ethyl-3-(phenoxymethyl)oxetane, and 3-(cyclohexyloxy)methyl-3-ethyloxetane. The oxetane compound may be used as the main component of a cationic polymerizable compound, or may be used in combination with an epoxy compound.
[0020] Examples of the vinyl compound include aliphatic or alicyclic vinyl ether compounds. For example, vinyl ethers of alkyl or alkenyl alcohols having 5 to 20 carbon atoms, such as n-amyl vinyl ether, i-amyl vinyl ether, n-hexyl vinyl ether, n-octyl vinyl ether, 2-ethylhexyl vinyl ether, n-dodecyl vinyl ether, stearyl vinyl ether, and oleyl vinyl ether; hydroxyl group-containing vinyl ethers, such as 2-hydroxyethyl vinyl ether, 3-hydroxypropyl vinyl ether, and 4-hydroxybutyl vinyl ether; vinyl ethers of monoalcohols having an aliphatic or aromatic ring, such as cyclohexyl vinyl ether, 2-methylcyclohexyl vinyl ether, cyclohexylmethyl vinyl ether, and benzyl vinyl ether; glycerol monovinyl ether, 1,4-butanediol monovinyl ether, 1,4-butanediol divinyl ether, and 1,6-hexanediol divinyl ether. vinyl ether, neopentyl glycol divinyl ether, pentaerythritol divinyl ether, pentaerythritol tetravinyl ether, trimethylolpropane divinyl ether, trimethylolpropane trivinyl ether, 1,4-dihydroxycyclohexane monovinyl ether, 1,4-dihydroxycyclohexane divinyl ether, 1,4-dihydroxymethylcyclohexane monovinyl ether, 1,4-dihydroxymethylcyclohexane divinyl ether, and other mono- to polyvinyl ethers of polyhydric alcohols; polyalkylene glycol mono- to divinyl ethers, such as diethylene glycol divinyl ether, triethylene glycol divinyl ether, and diethylene glycol monobutyl monovinyl ether; and other vinyl ethers, such as glycidyl vinyl ether and ethylene glycol vinyl ether methacrylate.
[0021] The cationic polymerization initiator is preferably a photo-cationic polymerization initiator. The photo-cationic polymerization initiator generates cationic species or Lewis acid by irradiation with active energy rays, and initiates the polymerization reaction of the cationic curable compound. The photo-cationic polymerization initiator acts catalytically with light, and therefore has excellent storage stability and workability even when mixed with the photo-cationic polymerizable compound. Examples of the photo-cationic polymerization initiator include onium salts such as aromatic iodonium salts and aromatic sulfonium salts, aromatic diazonium salts, and iron-arene complexes. The active energy ray-curable adhesive composition may use two or more kinds of cationic polymerization initiators. The content of the cationic polymerization initiator is usually 0.5 to 10 parts by mass with respect to 100 parts by mass of the cationic polymerizable compound.
[0022] The radical polymerizable compound refers to a compound or oligomer that undergoes radical polymerization reaction and hardens when irradiated with active energy rays or heated, and specifically includes compounds having ethylenic unsaturated bonds. Examples of compounds having ethylenic unsaturated bonds include (meth)acrylic compounds having one or more (meth)acryloyl groups in the molecule; vinyl compounds such as styrene, styrene sulfonic acid, vinyl acetate, vinyl propionate, and N-vinyl-2-pyrrolidone. Here, the (meth)acryloyl group means that it may be either an acryloyl group or a methacryloyl group, and the "(meth)" in other terms such as (meth)acrylate has the same meaning. The active energy ray-curable adhesive composition may contain two or more radically polymerizable compounds.
[0023] The radical polymerization initiator is preferably a photoradical polymerization initiator. The photoradical polymerization initiator initiates a polymerization reaction of a radically polymerizable compound by irradiation with active energy rays. Examples of the photoradical polymerization initiator include acetophenone-based initiators such as acetophenone and 3-methylacetophenone; benzophenone-based initiators such as benzophenone and 4-chlorobenzophenone; benzoin ether-based initiators such as benzoin propyl ether and benzoin ethyl ether; and thioxanthone-based initiators such as 4-isopropylthioxanthone. The active energy ray curable adhesive composition may use two or more types of photoradical polymerization initiators.
[0024] The active energy ray-curable composition may contain various additives as necessary, such as a sensitizer, an ion trapping agent, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow control agent, a plasticizer, and an antifoaming agent.
[0025] The first cured material layer 2 can be obtained, for example, by applying an active energy ray-curable adhesive composition onto the polarizing film 1 or the first resin film 3, and curing the applied active energy ray-curable adhesive composition by irradiating it with active energy rays. The active energy ray-curable adhesive composition can be applied by any known application method such as a doctor blade, a wire bar, a die coater, a comma coater, or a gravure coater.
[0026] The light source used for curing the active energy ray-curable adhesive composition is preferably a light source having an emission distribution at a wavelength of 400 nm or less, and examples of such light sources include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps. The light irradiation intensity when curing the active energy ray-curable adhesive composition can be appropriately set depending on the active energy ray-curable adhesive composition, but the light irradiation intensity in the wavelength region effective for activating the polymerization initiator is 0.1 to 1000 mW / cm. 2If the light irradiation intensity during the curing of the active energy ray-curable adhesive composition is too low, it will take a long time for the reaction to proceed sufficiently, and conversely, if the light irradiation intensity is too high, the heat radiated from the lamp and the heat generated during polymerization of the active energy ray-curable adhesive composition may cause deterioration of the attached film. The light irradiation time during the curing of the active energy ray-curable adhesive composition is not particularly limited, but the integrated light amount, which is expressed as the product of the light irradiation intensity and the light irradiation time, is preferably 10 to 5000 mJ / cm. 2 It is preferable to set the cumulative light amount so that: If the cumulative light amount is too small, the generation of active species derived from the polymerization initiator is insufficient, and the resulting curing may be insufficient. Also, if the cumulative light amount is too large, the irradiation time becomes very long, which is disadvantageous for improving productivity.
[0027] From the viewpoint of optical properties, the average refractive index of the first cured material layer 2 is preferably 1.59 or less, more preferably 1.55 or less, even more preferably 1.54 or less, and particularly preferably 1.51 or less. Also, it is preferably 1.49 or more, and more preferably 1.50 or more. The average refractive index of the first cured material layer 2 can be adjusted by appropriately selecting the type of polymerizable compound contained in the active energy ray-curable adhesive composition, the content thereof, etc. For example, when the active energy ray-curable adhesive composition is a photocationically polymerizable adhesive composition, the average refractive index of the first cured material layer 2 tends to be high by including a compound having a high refractive index, such as an alicyclic epoxy compound or an aromatic epoxy compound. The active energy ray-curable adhesive composition for forming the first cured material layer 2 is preferably a photocationically polymerizable curable adhesive composition or a photoradical polymerizable curable adhesive composition.
[0028] The thickness of the first cured material layer 2 is not particularly limited, but is preferably 0.1 μm or more, more preferably 0.5 μm or more, even more preferably 1 μm or more, and particularly preferably 2.1 μm or more. Also, the thickness is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less.
[0029] <First resin film> The first resin film 3 includes at least a film formed from a thermoplastic resin. The first resin film 3 may be formed from one layer, or may be formed from two or more layers. The first resin film 3 may be, for example, a single resin film formed from a thermoplastic resin, a laminated film in which a plurality of resin films formed from thermoplastic resins are laminated, or a film in which a resin film formed from a thermoplastic resin has a cured resin layer formed on at least one surface thereof. When the first resin film 3 is formed of a plurality of layers, the difference between the average refractive index of the layer in direct contact with the first cured material layer among the plurality of layers in the first resin film and the average refractive index of the first cured material layer may be 0.03 or less. For example, when the first resin film 3 is a two-layer film consisting of a resin cured layer and a resin film formed from a thermoplastic resin, if the layer in direct contact with the first cured material layer is the resin cured layer, the difference in refractive index between the resin cured layer and the first cured material layer may be 0.03 or less, and if the first cured material layer is in direct contact with a resin film formed from a thermoplastic resin, the difference in refractive index between the layer formed from a thermoplastic resin and the first cured material layer may be 0.03 or less.
[0030] Specific examples of films formed from thermoplastic resins include polyolefin resins such as polyethylene, polypropylene, and polymethylpentene; cyclic polyolefin resins having a cycloolefin or norbornene structure: fluorinated polyolefin resins such as polyvinyl fluoride, polyvinylidene fluoride, and polyfluorinated ethylene; polyester resins such as polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / isophthalate copolymers; polyamides such as nylon 6 and nylon 6,6; vinyl polymers such as polyvinyl chloride, vinyl chloride-vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, and vinylon; cellulose resins such as triacetyl cellulose, diacetyl cellulose, and cellophane; (meth)acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; and other resin films made of polystyrene, polycarbonate, polyarylate, polyimide, and the like.
[0031] The resin film formed from a thermoplastic resin may be a film formed from a composition containing the above-mentioned resin and additives, such as an ultraviolet absorber, an antioxidant, a surfactant, a plasticizer, a lubricant, and an antiblocking agent.
[0032] The average refractive index of a resin film formed from a thermoplastic resin can be adjusted by the type of resin, the degree of polymerization of the resin, etc. Alternatively, it may be adjusted by adding an additive to the resin.
[0033] The resin film formed from a thermoplastic resin is preferably a cellulose-based resin film, a (meth)acrylic-based resin film or a cycloolefin-based resin film, and more preferably a cycloolefin-based resin film.
[0034] When the first resin film 3 includes a resin cured layer, the resin cured layer is not particularly limited as long as the average refractive index difference is within a predetermined range, but is usually a layer formed from a resin composition and a layer of the cured product of the resin composition. Specific examples include a layer formed from a water-based resin composition and a layer formed from an active energy ray-curable composition.
[0035] The aqueous resin composition is not particularly limited, but contains at least a resin component, and the resin component is dissolved or dispersed in water. Examples of the resin forming the aqueous resin composition include polyvinyl alcohol resin, polyurethane resin, polyester resin, and acrylic resin having a crosslinkable functional group such as an oxazoline group. When the film formed from the thermoplastic resin is a cycloolefin resin film, the resin cured layer is preferably formed from a polyurethane resin from the viewpoint of adhesion to the film.
[0036] The polyurethane resin is typically a reaction product of a polyol and a polyisocyanate. As the polyol component, a polymer polyol such as a polyacrylic polyol obtained by polymerization of a (meth)acrylic acid ester and a hydroxyl group-containing monomer, a polyester polyol obtained by reaction of a polybasic acid and a polyol, or a polyether polyol obtained by reaction of a polybasic acid and a polyol is preferably used.
[0037] The polyurethane resin may have an acid structure. Examples of the acid structure include acid groups such as a carboxyl group (-COOH) and a sulfonic acid group (-SO3H). The acid structure may be present in a side chain or at a terminal in the polyurethane resin. One type of acid structure may be used, or two or more types may be used in combination at any ratio. The content of the acid structure is preferably 10 mgKOH / g to 250 mgKOH / g or less as an acid value in the polyurethane.
[0038] The polyurethane resin may be a commercially available product. Examples of commercially available products that can be used include the "ADEKA BONTITOR" series manufactured by ADEKA Corporation, the "OLESTAR" series manufactured by Mitsui Chemicals, Inc., the "BONDIC" series and "HYDRAN" series manufactured by Dainippon Ink and Chemicals, Inc., the "IMPLANILE" series manufactured by Bayer, the "POISE" series manufactured by Kao Corporation, the "SANPRENE" series manufactured by Sanyo Chemical Industries, Ltd., the "ISELAX" series manufactured by Hodogaya Chemical Co., Ltd., the "SUPERFLEX" series manufactured by Daiichi Kogyo Seiyaku Co., Ltd., the "NEOREZ" series manufactured by Zeneca, and the "Sancure" series manufactured by Lubrizol. The polyurethane may be used alone or in combination of two or more kinds in any ratio.
[0039] The aqueous resin composition may contain a crosslinking agent. As the crosslinking agent, any agent capable of reacting with the crosslinkable functional group of the polyurethane resin can be used without any particular limitation. When the polyurethane resin has a carboxy group, a crosslinking agent containing an amino group, an oxazoline group, an epoxy group, a carbodiimide group, or the like is used.
[0040] The aqueous resin composition may contain a base component. Examples of the base component include inorganic bases such as sodium hydroxide and potassium hydroxide; primary amine compounds, secondary amine compounds, tertiary amine compounds, hydrazide compounds, imidazoline compounds, and the like. Among them, compounds having a hydrazino group (-NHNH2 group) such as hydrazide compounds are preferred because they can appropriately improve the mechanical strength of the polyurethane resin layer. Examples of the hydrazide compounds include carbodihydrazide, oxalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, glycolic acid dihydrazide, polyacrylic acid dihydrazide, and the like.
[0041] The resin cured layer may be a film formed from a composition containing the above resin and additives, such as ultraviolet absorbers, antioxidants, surfactants, plasticizers, lubricants, antiblocking agents, inorganic particulate agents, and organic fine particles.
[0042] The average refractive index of the cured resin layer can be adjusted by the type of resin, the degree of polymerization of the resin, the type of crosslinking agent, etc. It may also be adjusted by adding an additive to the resin. The thickness of the cured resin layer is usually 0.01 to 5 μm, preferably 0.03 to 2 μm, and more preferably 0.05 to 0.5 μm.
[0043] The first resin film 3 may have a retardation value or may not have a retardation value. The first resin film 3 may have a retardation value in the plane or in the thickness direction. In-plane retardation R e and retardation R in the thickness direction th is defined by the following equations (1) and (2). R th = (n x +n y ) / 2-n z 〕×d (1) R e =(n x -n y )×d (2) (In the formula, n x is the refractive index in the slow axis direction (x-axis direction) in the film plane at a wavelength of 586 nm, and n y is the refractive index in the fast axis direction (the y axis direction perpendicular to the x axis in the film plane) at a wavelength of 586 nm, and n z is the refractive index in the thickness direction of the film (z-axis direction perpendicular to the film surface) at a wavelength of 586 nm, and d is the thickness of the film.
[0044] From the viewpoint of optical properties, the average refractive index of the first resin film 3 (the layer in direct contact with the first cured product layer when two or more layers are included) is preferably 1.44 to 1.57, more preferably 1.45 to 1.55, even more preferably 1.48 to 1.54, and particularly preferably 1.52 to 1.53.
[0045] From the viewpoint of ease of handling when laminating to a polarizing film, the thickness of the first resin film 3 is preferably 6 μm or more, more preferably 12 μm or more, even more preferably 20 μm or more, particularly preferably 40 μm or more, and is preferably 200 μm or less, more preferably 180 μm or less, even more preferably 150 μm or less, particularly preferably 100 μm or less. When the first resin film 3 is formed from a plurality of layers, the total thickness thereof may be within the above range.
[0046] <Polarizing film> The polarizing film 1 is a film that has a function of extracting linearly polarized light from incident natural light. Examples of the polarizing film 1 include a film in which a dichroic dye (preferably iodine) is contained in a polyvinyl alcohol-based resin film and is adsorbed and oriented. A film in which a dichroic dye is adsorbed and oriented in a polyvinyl alcohol-based resin film can be produced by a known method, and is usually produced through a step of uniaxially stretching a polyvinyl alcohol-based resin film, a step of dyeing the polyvinyl alcohol-based resin film with the dichroic dye to adsorb the dichroic dye, and a step of treating the polyvinyl alcohol-based resin film with the adsorbed dichroic dye with an aqueous boric acid solution. In addition, a film in which a dichroic dye is adsorbed and oriented in a polyvinyl alcohol-based resin film can also be obtained by a method described in, for example, JP 2012-159778 A.
[0047] The thickness of the polarizing film 1 is preferably from 3 to 30 μm, and more preferably from 10 to 25 μm.
[0048] The average refractive index of the polarizing film 1 is preferably equal to or greater than the average refractive index of the first cured product layer 2 . The average refractive index of the polarizing film 1 is preferably greater than that of the first resin film 3 .
[0049] <Second cured material layer> The pressure-sensitive adhesive layer-attached polarizing plate of the present invention may include a second cured material layer 4 on the surface of the polarizing film 1 opposite to the first cured material layer 2. Although there may be other layers between the second cured material layer 4 and the polarizing film 1, it is preferable that the second cured material layer 4 and the polarizing film 1 are in direct contact with each other. The second cured layer 4 is usually a layer formed from a resin composition, and is a cured layer of the resin composition. Specific examples thereof include a layer formed from a pressure-sensitive adhesive composition (pressure-sensitive adhesive layer), a layer formed from a water-based adhesive composition, and a layer formed from an active energy ray-curable composition. The resin composition forming the second cured material layer 4 may be the same as the resin composition forming the first cured material layer 2, or may be different. The second cured material layer 4 is preferably a layer formed from an active energy ray-curable composition.
[0050] <Second resin film> The second resin film 5 is preferably a film excellent in transparency, mechanical strength, thermal stability, moisture shielding property, isotropy, etc. Examples of the second resin film 5 include polyester-based polymers such as polyethylene terephthalate and polyethylene naphthalate; cellulose-based polymers such as diacetyl cellulose and triacetyl cellulose; acrylic polymers such as polymethyl methacrylate; styrene-based polymers such as polystyrene and acrylonitrile-styrene copolymer (AS resin); and polycarbonate-based polymers. In addition, examples of the second resin film 5 include polyolefins having a polyethylene, polypropylene, cyclo-based or norbornene structure; polyolefin-based polymers such as ethylene-propylene copolymers; amide-based polymers such as vinyl chloride-based polymers, nylon and aromatic polyamide; imide-based polymers, sulfone-based polymers, polyethersulfone-based polymers, polyetheretherketone-based polymers, polyphenylene sulfide-based polymers, vinyl alcohol-based polymers, vinylidene chloride-based polymers, vinyl butyral-based polymers, arylate-based polymers, polyoxymethylene-based polymers, epoxy-based polymers, and blends of the above polymers. The second resin film 5 and the first resin film 3 may be the same resin film or different resin films.
[0051] The second resin film 5 is preferably a film with low moisture permeability. The moisture permeability of the second resin film 5 is preferably 800 g / (m 2 24 hours) or less, and more preferably 600g / (m 2 24 hours) or less, more preferably 400g / (m 2 24 hours) or less, particularly preferably 200 g / (m 2 24 hours) or less, and particularly preferably 100 g / (m 2 When the moisture permeability of the second resin film 5 is equal to or less than the above value, it is possible to prevent the intrusion of moisture from the outside under high temperature and high humidity conditions and to prevent the acceleration of the migration of the dichroic dye (iodine) contained in the polarizing film 1, thereby more effectively preventing the deterioration of the optical properties.
[0052] The thickness of the second resin film 5 is not particularly limited, but is usually 5 to 500 μm, preferably 1 to 300 μm, more preferably 5 to 200 μm, and further preferably 10 to 100 μm.
[0053] <Adhesive layer> The pressure-sensitive adhesive layer 6 may be a layer formed from a known pressure-sensitive adhesive composition. Examples of the pressure-sensitive adhesive composition include pressure-sensitive adhesive compositions having an acrylic resin, a rubber resin, a urethane resin, a silicone resin, a polyvinyl ether resin, or the like as a base polymer. The pressure-sensitive adhesive composition may be an energy ray-curable pressure-sensitive adhesive composition or a heat-curable pressure-sensitive adhesive composition. The adhesive composition forming the adhesive layer 6 is preferably an acrylic adhesive composition that uses an acrylic resin as a base polymer, which is excellent in transparency, adhesive strength, reworkability, weather resistance, heat resistance, and the like.
[0054] The adhesive layer 6 can be provided by a method in which the adhesive composition is dissolved in an organic solvent, applied to the first resin film 4 using a die coater, gravure coater or the like, and then dried. Alternatively, the adhesive layer 6 can be provided by a method in which a sheet-shaped adhesive composition formed on a plastic film (called a separate film) that has been subjected to a release treatment is transferred to the first resin film 4.
[0055] The thickness of the pressure-sensitive adhesive layer 6 is not particularly limited, but is preferably within the range of 2 to 40 μm, more preferably within the range of 5 to 35 μm, and even more preferably within the range of 10 to 30 μm.
[0056] The pressure-sensitive adhesive layer 6 preferably has a storage modulus of 0.10 to 5.0 MPa at 23 to 80°C, more preferably 0.15 to 1.0 MPa. If the storage modulus at 23 to 80°C is 0.10 MPa or more, white spots due to shrinkage of the pressure-sensitive adhesive layer-attached polarizing plate when the liquid crystal display panel including the pressure-sensitive adhesive layer-attached polarizing plate is exposed to high temperatures or the like can be suppressed, which is preferable. Also, if the storage modulus is 5 MPa or less, it is preferable because durability is less likely to decrease due to a decrease in adhesive strength. Here, "exhibiting a storage modulus of 0.10 to 5.0 MPa at 23 to 80°C" means that the storage modulus has a value in the above range at any temperature in this range. Since the storage modulus usually decreases gradually with increasing temperature, if the storage modulus at 23°C and 80°C is both within the above range, it can be considered that the pressure-sensitive adhesive layer exhibits a storage modulus in the above range at this temperature range. The storage modulus of the adhesive layer can be measured using a commercially available viscoelasticity measuring device, for example, a viscoelasticity measuring device "DYNAMIC ANALYZER RDA II" manufactured by REOMETRIC.
[0057] The average refractive index of the pressure-sensitive adhesive layer 6 is preferably 1.45 to 1.49, and more preferably 1.46 to 1.47. The average refractive index value of the pressure-sensitive adhesive layer 6 is preferably the same as or smaller than the average refractive index value of the first resin film 3. The difference between the average refractive index of the pressure-sensitive adhesive layer 6 and the average refractive index of the first resin film 3 is preferably 0.12 or less, more preferably 0.10 or less, and even more preferably 0.08 or less. The average refractive index of the pressure-sensitive adhesive layer 6 can be adjusted by changing the type of base polymer or the type of crosslinking agent.
[0058] The present invention also includes an image display device in which the polarizing plate with the pressure-sensitive adhesive layer of the present invention and an image display panel are laminated. The polarizing plate with the pressure-sensitive adhesive layer of the present invention is preferably laminated on the viewing side of the image display panel (the side opposite to the backlight in the case of a liquid crystal display panel). The image display panel may be a liquid crystal display panel or an organic EL display panel. EXAMPLES
[0059] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "%" and "parts" respectively represent "% by mass" and "parts by mass" unless otherwise specified.
[0060] <Method for measuring the refractive index of active energy ray curing adhesive> The active energy ray curing adhesive was applied to one side of a stretched norbornene resin film ("ZEONORFILM" manufactured by Zeon Corporation) using a bar coater (manufactured by Daiichi Rika Co., Ltd.), and the adhesive was then exposed to an integrated light dose of 600 mJ / cm using an ultraviolet ray irradiation device (manufactured by Fusion UV Systems Co., Ltd.). 2 The coating was then irradiated with UV-B light to obtain a cured product, which had a thickness of approximately 30 μm. The norbornene-based resin film was peeled off from the obtained cured product, and the refractive index (wavelength 589 nm) of the cured product layer was measured in a 25° C. environment using a multi-wavelength Abbe refractometer ("DR-M2" manufactured by Atago Co., Ltd.). The refractive index of the cured product of the active energy ray-curable adhesive a was 1.54, and the refractive index of the cured product of the active energy ray-curable adhesive b was 1.51.
[0061] <Production Example 1: Production of polarizing film> A polyvinyl alcohol film with an average degree of polymerization of about 2,400, a degree of saponification of 99.9 mol% or more, and a thickness of 75 μm was immersed in pure water at 30° C., and then immersed in an aqueous solution of iodine / potassium iodide / water with a mass ratio of 0.02 / 2 / 100 at 30° C. to perform iodine dyeing (iodine dyeing step).The polyvinyl alcohol film that had undergone the iodine dyeing step was immersed in an aqueous solution of potassium iodide / boric acid / water with a mass ratio of 12 / 5 / 100 at 56.5° C. to perform boric acid treatment (boric acid treatment step). The polyvinyl alcohol film that had been subjected to the boric acid treatment step was washed with pure water at 8°C and then dried at 65°C to obtain a polarizer in which iodine was adsorbed and aligned in the polyvinyl alcohol. At this time, stretching was performed in the iodine dyeing step and the boric acid treatment step. The total stretching ratio in this stretching was 5.3 times, and the thickness of the obtained polarizer was 27 μm.
[0062] <Preparation Example 1: Preparation of polarizing plate> The resin films used in the preparation of the polarizing plate are as follows. Film A: 80 μm film made of (meth)acrylic resin Film B: A film made of a cycloolefin resin with an average refractive index of 1.53 at 50 μm (in-plane retardation Re = 50 nm, thickness retardation Rth = 135 nm) Film C: A cycloolefin resin film (film B) having a resin cured layer X with a thickness of 50 nm and an average refractive index of 1.57 formed on one surface thereof.
[0063] One side of film A was subjected to a corona discharge treatment, and the active energy ray curable composition b was applied to the corona discharge treated surface so that the thickness after curing was about 3.5 μm. Then, the polarizer prepared in Production Example 1 was laminated to the coated surface. Next, one side of film B was subjected to a corona discharge treatment, and the active energy ray curable composition a was applied to the corona discharge treated surface so that the thickness after curing was about 2.5 μm. The polarizer with film A prepared above was placed on the coated surface on the polarizer side, and pressed and laminated using a lamination roll to obtain a laminate. The obtained laminate was irradiated from the film B side with an ultraviolet ray irradiation device equipped with a belt conveyor (the lamp used was a "D bulb" manufactured by Fusion UV Systems Co., Ltd.) with an accumulated light amount of 400 mJ / cm2. 2 The polarizing plate was fabricated by irradiating the film with ultraviolet light so that the optical properties of the film were such ...
[0064] Example 1: Preparation of a polarizing plate with an adhesive layer An organic solvent solution of an acrylic adhesive was applied to the release-treated surface of a 38 μm-thick polyethylene terephthalate film using a die coater, and then dried to prepare a sheet-like adhesive layer with a release film. The thickness of the adhesive layer was 20 μm. The release film was peeled off from the prepared sheet-like adhesive layer, and the refractive index of the adhesive layer (wavelength 589 nm) was measured using a multi-wavelength Abbe refractometer ("DR-M2" manufactured by Atago Co., Ltd.) in an environment of 25° C. The refractive index of the adhesive layer was 1.47.
[0065] <Preparation of polarizing plate with adhesive layer> The surface of film B (first resin film) of the polarizing plate was subjected to a corona treatment, and the surface (adhesive surface) of the sheet-like adhesive prepared in Preparation Example 2 opposite to the release film was laminated with a laminator, and then cured for 7 days under conditions of a temperature of 23°C and a relative humidity of 65% to obtain a polarizing plate with an adhesive layer. This laminate has a configuration in which a release film is laminated onto the adhesive layer.
[0066] <Creating sheets> Using a cutting device (Ogino Seiki Seisakusho, Super Cutter "PN1-600"), the above-mentioned polarizing plate with adhesive layer was cut from the film A side so that the length in the stretching direction (MD) of the polarizer and the length in the direction intersecting the stretching direction of the polarizer (TD) were 50 mm.
[0067] <Edge light leakage evaluation> After peeling off the release film from the obtained polarizing plate with the adhesive layer, the adhesive layer surface was attached to the center of a 0.7 mm thick glass substrate ["Eagle XG" manufactured by Corning] to obtain a laminate. The obtained laminate was placed on the backlight so that a 10 mm (MD) x 50 mm (TD) polarizing plate portion of the 50 mm x 50 mm was protruding from the bright part of the backlight. Next, the polarizing plate (40 mm x 50 mm) in the bright part of the backlight and the entire bright part of the backlight were covered with a black acrylic plate. The backlight was turned on, and the edge of the polarizing plate was visually confirmed from an angle of 85° (θ = 85° in Figure 3) to the side from the front of the polarizing plate. The results were judged according to the following criteria. The results are shown in Table 1. <Light leakage criteria> ○: Almost no light leakage is visible. △: Light leakage is weak and visible. ×: Light leakage is clearly visible.
[0068] Example 2: Manufacture of polarizing plate Except for using the curable composition b as the composition for forming the first cured product layer, a polarizing plate with a pressure-sensitive adhesive layer was produced in the same manner as in Example 1, and the same evaluation was performed. The results are shown in Table 1.
[0069] Example 3: Manufacture of polarizing plate One side of film A was subjected to a corona discharge treatment, and the active energy ray curable composition b was applied to the corona discharge treated surface so that the thickness after curing was about 3.5 μm. Then, the polarizer prepared in Production Example 1 was laminated to the coated surface. Next, the cycloolefin resin film surface of film C was subjected to a corona discharge treatment, and the active energy ray curable composition b was applied to the corona discharge treated surface so that the thickness after curing was about 2.5 μm. The polarizer with film A prepared above was placed on the coated surface on the polarizer side, and pressed and laminated using a lamination roll to obtain a laminate. The obtained laminate was irradiated from the film C side with an ultraviolet ray irradiation device equipped with a belt conveyor (the lamp used was a "D bulb" manufactured by Fusion UV Systems Co., Ltd.) with an accumulated light amount of 400 mJ / cm 2 The polarizing plate was fabricated by irradiating the film with ultraviolet light so that the optical properties of the film were such ... A pressure-sensitive adhesive layer was formed on the surface of the cured resin layer X in the same manner as in Example 1, and evaluation was carried out. The results are shown in Table 1.
[0070] Example 4: Manufacture of polarizing plate A polarizing plate was produced in the same manner as in Example 3, except that the resin cured layer X surface of the film C was subjected to a corona discharge treatment, and the active energy ray-curable curable composition a was applied to the corona discharge-treated surface so as to have a thickness of about 2.5 μm after curing. The obtained polarizing plate had a structure of Film A (second resin film) / cured layer of curable composition b (second cured layer) / polarizing film / cured layer of curable composition a (first cured layer) / Film C (resin cured layer X / cycloolefin resin film), and the absolute value of the refractive index difference between the first cured layer and the resin cured layer X was 0.03. A pressure-sensitive adhesive layer was formed on the surface of a cycloolefin resin film and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0071] Comparative Example 1: Manufacture of polarizing plate A polarizing plate with an adhesive layer was prepared in the same manner as in Example 4, except that the active energy ray curable composition a was replaced with the active energy ray curable composition b, and the same evaluation was performed. The structure of the obtained polarizing plate with an adhesive layer was film A (second resin film) / cured layer of curable composition b (second cured layer) / polarizing film / cured layer of curable composition b (first cured layer) / film C (resin cured layer X / cycloolefin resin film) / adhesive layer, and the absolute value of the refractive index difference between the first cured layer and the resin cured layer was 0.06. The results are shown in Table 1.
[0072] [Table 1]
[0073] The polarizing plate with a pressure-sensitive adhesive layer of the present invention suppresses light leakage even when viewed from approximately the side at an angle of 85° from the surface of the polarizing plate. Therefore, when the polarizing plate with a pressure-sensitive adhesive layer of the present invention is incorporated into a display device in which the height of the bezel provided in the display device is reduced or the bezel is omitted, light leakage is suppressed even if the edge of the polarizing plate is exposed. [Industrial Applicability]
[0074] The polarizing plate with an adhesive layer of the present invention is useful because it has little light leakage from the ends of the polarizing plate, even when incorporated into a display device with a narrow bezel width, a display device with a low bezel height, or a display device that omits the bezel. [Explanation of symbols]
[0075] 1. Polarizing film 2 First cured material layer 3. First resin film 4 Second cured material layer 5. Second resin film 6 Adhesive layer 7 Image display panel 10 Polarizing plate 20 Polarizing plate with adhesive layer 30 Image display device θ Angle from the front of the polarizing plate
Claims
1. A polarizing plate with a pressure-sensitive adhesive layer, comprising a polarizing film, a first cured material layer, a first resin film, and a pressure-sensitive adhesive layer in this order, the polarizing film and the first cured material layer are in direct contact with each other, the first cured material layer and the first resin film are in direct contact with each other, the first resin film and the pressure-sensitive adhesive layer are in direct contact with each other, The thickness of the first resin film is 20 μm or more, The thickness of the first cured material layer is 10 μm or less, The average refractive index of the first cured material layer is 1.49 or more and 1.59 or less, an absolute value of a difference between an average refractive index of the first cured material layer and an average refractive index of the first resin film is 0.03 or less; A polarizing plate with a pressure-sensitive adhesive layer, in which the difference between the average refractive index of the pressure-sensitive adhesive layer and the average refractive index of the first resin film is 0.08 or less.
2. 2. The polarizing plate according to claim 1, wherein the first cured material layer is a cured material of an active energy ray-curable adhesive composition.
3. 3. The polarizing plate according to claim 1, wherein the first resin film comprises a film formed from a thermoplastic resin.
4. 4. The polarizing plate according to claim 1, further comprising a second resin film on a surface of the polarizing film opposite to the first cured material layer via a second cured material layer.
5. 5. An image display device comprising: an image display panel; and the pressure-sensitive adhesive layer-attached polarizing plate according to claim 1, which is disposed on a viewing side of the image display panel.
Citation Information
Patent Citations
Laminated wavelength plate, circularly polarized light plate and liquid crystal display device
JP1999149015A
Polarizing element
JP2003307622A
Polarizing plate and liquid crystal display device
JP2005521100A
Polarizing plate and manufacturing method therefor
JP2009042383A
Optical isotropic protective film for polarizing film, and polarizing plate
JP2013033237A